PELATIHAN DESAIN KEMASAN (PACKAGING) DAN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK UMKM KAPANEWON TURI - Bahri Bahri; Niken Permata Sari; Fikri Alamsyah (As-Sidanah, 2023)
The product development strategy is carried out by the innovation of packaging sizes (variations in price, size, and appearance); Packaging Color Innovation (light blue, red, green, purple, and yellow); Innovation of Packaging Materials (cans, aluminum, glass, plastic paper, boxes, and jars); Packaging Label Innovation (selection of colors, illustrations, letters, images); and Packaging Shape Innovation (graphic design, shape, and size). Digital marketing is done through Tokopedia's e-commerce. The pre-test results were dominated by 14 members or 32% did not understand how to design product packaging. From the post-test results after giving the material, there was a change in the results of 27 people, or 63% "Very Knowing" how to innovate products through changes in packaging materials from Plastic to Eye Catching Pouch Materials, listing brands, names, labels and logos on product packaging, creating Tokopedia, Instagram, and Facebook to increase sales. The changes that have been made impact an increase in sales by 85% after Covid-19.